2008
DOI: 10.1243/09544100jaero406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blade tip cutting on axial compressor aerodynamic performance

Abstract: The purpose of this article is to numerically investigate the function of blade tip cutting on axial flow compressors. The subject of this article is a subsonic compressor stage built and tested by Northwest Polytechnic University. The effect of cutting material from the blade pressure side is first analysed as an isolated rotor, and then in the environment of a stage with a downstream stator. The tool used for simulation is commercial computational fluid dynamics package of NUMECA.The numerical results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Contrary to this, model B had the higher pressure ratio in a larger area than the other models. Figure 6 also depicts that the modifications of the CB were strongly influential on the pressure around the root area, as reported in [1,15]. For further analysis, the results in Figure 6 were normalized with the pressure ratio of model A at the same positions and then reported in Figure 7 for blade spans of (a) 95.5%, (b) 95.8%, (c) 96.0%, and (d) 96.5%.…”
Section: Aerodynamicsmentioning
confidence: 79%
See 2 more Smart Citations
“…Contrary to this, model B had the higher pressure ratio in a larger area than the other models. Figure 6 also depicts that the modifications of the CB were strongly influential on the pressure around the root area, as reported in [1,15]. For further analysis, the results in Figure 6 were normalized with the pressure ratio of model A at the same positions and then reported in Figure 7 for blade spans of (a) 95.5%, (b) 95.8%, (c) 96.0%, and (d) 96.5%.…”
Section: Aerodynamicsmentioning
confidence: 79%
“…Finally, fatigue analysis has been employed to predict the damage, life, and safety factor of the CB [11,12]. For the AD, CFD can simulate the C l , C d , pressure, vector flow, and other variables in the compressor stage [1,[13][14][15][16][17]. From previous computer simulations, it has been indicated that inappropriate modifications can lead to inefficiency of the generator and also shorten its lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, the EJ200 [7] and the GE9X [8] engines have implemented squealered tip on more than one stage in high-pressure compressors and both engines utilize suction side squealers (SSS), while no pressure side squealer (PSS) has been found in use. Some researchers, through experiments [9][10][11] and numerical simulation [6,[10][11][12][13][14][15][16] on both compressor cascade and rotational compressor rotor, have agreed that compressor blades with SSS show better aerodynamic performance than these with flat tip, although the squealered tips used by different researchers vary greatly in geometry. Also SSS helps to improve the loading of the blade tip and therefore leads to higher pressure rise.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, tip geometry also helps to reduce tip leakage flow and improves efficiency. Lu et al [12] found that aerodynamic performance is very sensitive to the shape of squealer exit. One deliberately designed geometry of SSS, which performs well in single row simulation, causes reduction of performance when it is put into a stage simulation.…”
Section: Introductionmentioning
confidence: 99%